POSSIBILITIES FOR OPTIMIZATION OF CIRCUIT ACCELERATING OPERATION OF ELECTROMAGNETS - S. S. Stoyanova (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper reveals an accelerating circuit for electromagnet operation with the help of an additional resistor R that is shunted with a capacitor C. Resistor R is connected in series with the electromagnet winding. The possibility of the circuit optimization has been substantiated with the purpose to limit the final speed with which a movable part of the electromagnet reaches a limiter. Such circuit may find its application in relay protection.